2009
DOI: 10.1111/j.1476-5381.2008.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of ecto‐ATPase and ecto‐ATPDase pathways to the biphasic effect of ATP on acetylcholine release from myenteric motoneurons

Abstract: Background and purpose:The relative contribution of distinct ecto-nucleotidases to the modulation of purinergic signalling may depend on differential tissue distribution and substrate preference. Experimental approach: Extracellular ATP catabolism (assessed by high-performance liquid chromatography) and its influence on [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 53 publications
2
45
0
Order By: Relevance
“…Given our previous findings suggesting that excitatory A 2A receptors are preferentially activated by adenosine formed from released adenine nucleotides in rat hippocampal, neuromuscular and myenteric synapses [31,41], we evaluated the amount and distribution of ecto-5′-nucleotidase/CD73 in the human hippocampus compared to those of the A 2A receptor, as this is the rate limiting enzyme for extracellular adenosine formation in the brain. Figure 5a shows that the hippocampus of MTLE patients exhibits higher (P < 0.001) amounts of ecto-5′-nucleotidase/CD73 protein (∼55 kDa) than control individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given our previous findings suggesting that excitatory A 2A receptors are preferentially activated by adenosine formed from released adenine nucleotides in rat hippocampal, neuromuscular and myenteric synapses [31,41], we evaluated the amount and distribution of ecto-5′-nucleotidase/CD73 in the human hippocampus compared to those of the A 2A receptor, as this is the rate limiting enzyme for extracellular adenosine formation in the brain. Figure 5a shows that the hippocampus of MTLE patients exhibits higher (P < 0.001) amounts of ecto-5′-nucleotidase/CD73 protein (∼55 kDa) than control individuals.…”
Section: Resultsmentioning
confidence: 99%
“…This may be critical for A 2A receptor activation because adenosine resulting from the extracellular catabolism of released ATP, via the ecto-5′-nucleotidase/ CD73 pathway, preferentially activates this receptor subtype in the hippocampus and other excitatory synapses (e.g., neuromuscular junction, myenteric plexus) [31,41]. The tight association between ecto-5′-nucleotidase/CD73 and the A 2A receptor has been elegantly and definitively documented by co-immunoprecipitation and proximity ligation assays in the striatum [45].…”
Section: Discussionmentioning
confidence: 99%
“…Morphological data on P2 receptor distribution in the gut are scarce. At least in the mouse ileum, smooth muscle cells were strongly immunoreactive for P2Y 1 receptors [7] , and myenteric plexus neurons in the guinea-pig ileum were shown to express the P2Y 6 and P2Y 12 receptor [36] . However, interspecies differences are very likely, because α,β-Me-ATP-induced contractions of guinea-pig ileum were sensitive to the P2X 1 receptor antagonist NF279 and the P2X receptor-preferring blocker PPADS [37] .…”
Section: Wwwchinapharcom Mader F Et Almentioning
confidence: 99%
“…Post-junctional P2Y receptors, however, activate apamin-sensitive SK channels as a consequence of Ca 2+ release from thapsigargin-sensitive stores and thus promote relaxation [4,9,19,20] . Recently, an elegant study tested the hypothesis that spontaneous hydrolysis products of ATP, such as ADP and adenosine, mediate the biphasic effects observed following ATP administration and found that ADP and adenosine were agonists of P2Y and adenosine A 1 receptor, respectively, thereby having the opposite effects from ATP [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation